2018
DOI: 10.12659/msm.908425
|View full text |Cite
|
Sign up to set email alerts
|

Lead Induces Genotoxicity via Oxidative Stress and Promoter Methylation of DNA Repair Genes in Human Lymphoblastoid TK6 Cells

Abstract: BackgroundLead (Pb) is a widely used metal in modern industry and is regarded as a health hazard. Although lead-induced genotoxicity has been confirmed, the direct evidence that lead induces genotoxicity in human cells and its related mechanisms has not been fully elucidated. In this study, for the first time, we evaluated the genotoxicity induced by lead in human lymphoblastoid TK6 cells.Material/MethodsThe TK6 cells were incubated with various concentrations of Pb(Ac)2 for 6 h, 12 h, or 24 h. Cell viability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 47 publications
(39 reference statements)
0
13
0
Order By: Relevance
“…Moreover, when Nrf2 was silenced in microglia and then exposed to Pb, ROS production was higher and the cell viability decreases, suggesting that Nrf2 plays a protective role against Pb toxicity in microglia [ 168 ]. Parallelly, oxidative stress induced by Pb exposure has been shown, and, regardless of the activation of the Nrf2-ARE signaling pathway, oxidative DNA damage occurs and is exacerbated by promoter methylation of DNA repair genes in human lymphoblastoid TK6 cells [ 169 ]. Nrf2 protective role against oxidative stress induced by Pb has also been demonstrated in SH-Sy5Y cells.…”
Section: Mechanisms Related To Cognitive Impairment Induced By Pb mentioning
confidence: 99%
“…Moreover, when Nrf2 was silenced in microglia and then exposed to Pb, ROS production was higher and the cell viability decreases, suggesting that Nrf2 plays a protective role against Pb toxicity in microglia [ 168 ]. Parallelly, oxidative stress induced by Pb exposure has been shown, and, regardless of the activation of the Nrf2-ARE signaling pathway, oxidative DNA damage occurs and is exacerbated by promoter methylation of DNA repair genes in human lymphoblastoid TK6 cells [ 169 ]. Nrf2 protective role against oxidative stress induced by Pb has also been demonstrated in SH-Sy5Y cells.…”
Section: Mechanisms Related To Cognitive Impairment Induced By Pb mentioning
confidence: 99%
“…Although Zinc can function as a member of antioxidant properties, it generates reactive oxygen species when yeast cells were exposed to high zinc levels (Pagani et al 2007;Powell 2000;Hao and Maret 2005). Moreover, metal toxicities are often attributed mainly to the capacity to induce the unfolded protein response (UPR), the oxidative stress, DNA damage or even cell death (Nargund et al 2008;Muthukumar and Nachiappan 2010;Liu et al 2018). High intracellular ROS levels induced by zinc or other metals and stresses can trigger several biological molecules, such as DNA damage, lipid peroxidation and depletion of protein sulphydryl (Howlett and Avery 1997;Chrestensen et al 2000;Serero et al 2008).…”
mentioning
confidence: 99%
“…It has been reported that 8‐hydroxydeoxyguanosine (8‐OhdG), a molecular marker for DNA oxidative damage was significantly increased in the urine of occupationally manifested individuals (Pawlas et al, ). A recent study by Lui et al () demonstrated that Pb produced genotoxic effects through increased oxidative damage and reduced the expression of genes involved in DNA repair by promotor methylation in human lymphoblastoid TK6 cell. A remarkable increase in the malondialdehyde (MDA) level and decrease in the endogenous antioxidants reserve had been evaluated following ingestion of Pb acetate in rodents (Aziz, ).…”
Section: Discussionmentioning
confidence: 99%